1997
DOI: 10.1016/s0029-7844(97)00228-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional Papanicolaou smears and a fluid-based, thin-layer system for cervical cancer screening

Abstract: The fluid-based, ThinPrep method of sample preparation resulted in a statistically significant increase in cytologic diagnosis of cervical cancer precursors and in specimen adequacy compared with the conventional Papanicolaou testing method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
108
1
5

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(116 citation statements)
references
References 14 publications
2
108
1
5
Order By: Relevance
“…It is very well known that up to 90% of the Pap material collected by health providers remains unused by pathologists for diagnosis [26,27,28,29,30]. In fact, one of the attractive points for switching from conventional to liquid-based technology was the improved ability of capturing more material for a more accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is very well known that up to 90% of the Pap material collected by health providers remains unused by pathologists for diagnosis [26,27,28,29,30]. In fact, one of the attractive points for switching from conventional to liquid-based technology was the improved ability of capturing more material for a more accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cells processed with LBP seem to be over-stained compared with those processed conventionally. It is said [10 ]that the cells processed with SurePath [1,2] demonstrate a tendency towards shrinkage due to ethanol fixation, whereas those with ThinPrep do not [3,4,5]. The shrinkage of cells with the TACAS procedure may be in the range between these two methods.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid-based cytological procedures [1,2,3,4,5,6] have become more widely used for cervical cancer screening, which may be due to the clear cytological specimens in the limited field of the glass slide that are produced with an automated smearing system. A new liquid-based procedure (LBP), the Thinlayer Advanced Cytology Assay System (TACAS™; MBL, Nagano, Japan), is now commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] In each trial both conventional and ThinPrep slides were prepared. This involved the clinician first making a conventional smear on a microscope slide and then rinsing the instruments containing the remaining cellular material into a vial containing PreservCyt solution to make a ThinPrep slide as outlined above.…”
Section: Introductionmentioning
confidence: 99%
“…ThinPrep was found to be superior to the conventional technique in the detection of low-grade epithelial abnormalities. 13,14,18,19 In a study comparing the ThinPrep technique with histology (gold standard), ThinPrep was shown to be significantly more sensitive than the conventional method for the detection of lowgrade squamous intraepithelial lesion (SIL) and more severe diseases. 22 The ThinPrep method showed no significant difference in specificity from the conventional method.…”
Section: Introductionmentioning
confidence: 99%